Connecting Engineering Students with the Library: A Case Study in Active Learning - Brian D. Quigley; Jean McKenzie (Issues in Science and Technology Librarianship)
When asked to provide library instruction to Technical Communication classes, the authors developed a lecture and demonstration covering information literacy, the research process and relevant electronic resources. During the first classes, it became obvious that neither the lecture format nor the content met the instructional objectives. This article delineates the evolution of these classes from lectures to active learning classes. Working closely with the instructors, the authors have developed classes to meet four library instruction objectives in the context of course goals and assignments. The changes have been guided by feedback from instructors and students, as well as the continuing education and cumulative experience of the authors as teachers.